PEMBELAJARAN BAHASA INGGRIS DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DI SEKOLAH MENENGAH ATAS NEGERI 2 KOTA MADIUN - Agus Budi Santoso; Sumani Sumani (Jurnal Pendidikan, 2008)
This   research    serves   a  thorough    discussion     on:   1)  the implementation    of  Contextual   Teaching  and  Learning  for  English subject; 2) the implementation of evaluation under Contextual Teaching and Learning  for English  subject.This   research   is  conducted     at  SMA   Negeri   2  Madiun Municipality   by the descriptive-qualitative    method under naturalistic research  design. The source  of data are:  1) events,  2) informers,  and, 3) files.  The  strategies  of accumulating-the data are observation,   in- depth  interview   and  documents   investigation.   Clipping   technique used   in  this   research    is  the  criterion-based    selection.    Source triangulation   is used to guarantee  the data validity. The data analysis is carried  out by the use of Miles and Huberman's  interactive analysis.The  analysis  results  in conclusions   that: the implementation, of contextual  teaching  and learning includes three steps, i.e. planning, implementing    and  evaluating.   In the  planning   stage,  the  teachers get the  lesson  plans  from  the teachers'   association   so as to get the uniformity  in format for all of English teachers in Madiun Municipality. The  standardization      of  lesson   plan  format   throughout    Madiun Municipality    is against   the  principles   of contextual   teaching   and learning.  In the implementation   stage, it is shown that teachers  do not completely  implement  the principle of contextual  teaching an learning due  to the  lack  of teachers'   knowledge   in contextual   teaching  and learning   principles.    The  authentic   assessment    suggested   by  the contextual    teaching   and  learning   can  not  either   be  implemented satisfactorily    by  the  teachers.   Two out  of  other reasons   are: that firstly, authentic  assessment  is regarded  difficult  to carry out because of the  lack  of facilities  for this.  Secondly,  the teachers  are mostly discouraged   by the inaction  of standardized   national test, which  is believed   of  confronting    the  essence   of  contextual    teaching   and learning  evaluation   system.  They  are so determined   if the learning and teaching  process  are mainly  supposed  to make  the students  get the high scores  in the standardized   national  test that they forget  the principles  of contextual  teaching  and learning.